Label-free microfluidic blood cells micro-separator - Aissa, Foughalia; Ibrahim, Siti Noorjannah (IEEE, 2016)
Blood cells separation is of great interest in many biomedical applications because of its importance in sample preparation for both clinical diagnosis and therapeutic research. In this work, the micro-separator uses the combination of magnetophoresis with hydrodynamics in order to separate white blood cells (WBCs) and red blood cells (RBCs) by taking into account the magnetization of the ferromagnetic elements and fluidic forces on the cells. The microfluidic devices can achieve label-free, continuous separation of WBCs and RBCs with relatively high efficiency. The micro-separator utilizes hydrodynamic force acting on cells within laminar flow, coupled with magnetophoresis force in novel U-shaped micro-channel. Here, we report the separation efficiency of the microfluidic device in continuous flow based on results of a 3D model simulation conducted in COMSOL Multiphysics. The proposed device enables label-free cell separation and thus, it can be a useful microfluidic component for lab-on-a-chip system and integrated biological and biomedical applications.